2007
DOI: 10.1038/sj.mt.6300032
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Transduction is Required for the Correction of Diabetes Using Pdx-1 or Neurogenin-3 in the Liver

Abstract: The regeneration of insulin-producing cells in vivo has emerged as a promising method for treating type I diabetes. Pancreatic duodenal homeobox-1 (Pdx-1), NeuroD, and Neurogenin-3 (Ngn3) are pancreatic transcription factors important for the development of insulin-producing cells in the liver. Other groups have demonstrated that adenoviral-mediated transgene expression of these transcription factors in the liver can reverse hyperglycemia in diabetic mice. We delivered Pdx-1 and Ngn3 to the livers of diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
90
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 39 publications
2
90
0
1
Order By: Relevance
“…Chen et al (2009) have reported that the hydrodynamic delivery of Pdx1 alone in a commercially available plasmid (pcDNA 3.1, Invitrogen) to hyperglycaemic mice resulted in insulin-positive cells by immunohistology in the liver at week 1 but not week 2 after gene delivery. By contrast, Wang et al (2007) did not obtain insulin expression in liver by hydrodynamic delivery of Pdx1 alone in hyperglycaemic mice, using a plasmid containing an alpha1-antitrypsin promoter and liver-specific enhancer (Argyros et al 2008). It is difficult to compare these studies, other than to note the different results with the different plasmids in hyperglycaemic mice.…”
Section: Discussionmentioning
confidence: 82%
“…Chen et al (2009) have reported that the hydrodynamic delivery of Pdx1 alone in a commercially available plasmid (pcDNA 3.1, Invitrogen) to hyperglycaemic mice resulted in insulin-positive cells by immunohistology in the liver at week 1 but not week 2 after gene delivery. By contrast, Wang et al (2007) did not obtain insulin expression in liver by hydrodynamic delivery of Pdx1 alone in hyperglycaemic mice, using a plasmid containing an alpha1-antitrypsin promoter and liver-specific enhancer (Argyros et al 2008). It is difficult to compare these studies, other than to note the different results with the different plasmids in hyperglycaemic mice.…”
Section: Discussionmentioning
confidence: 82%
“…An intriguing observation in the field has been that often times reprogramming is seemingly dependent on the activation of immune/innate responses in the host cells. This was evidenced by the fact that the adenoassociated virus (AAV)-mediated delivery of such factors failed to induce liver-to-pancreas transdifferentiation, whereas plasmids plus an irrelevant adenovirus (which are much more immunogenic than AAVs) did (103).…”
Section: Cell Reprogrammingmentioning
confidence: 99%
“…Whether these observations were reflective of the reprogramming of terminal hepatocytes or the differentiation of resident progenitor/stem cells was not clear at the time, and in vitro experiments did not prove to be much more informative (96). Additional reports established that combining Pdx1 with other transcription factors, such as BETA2/NeuroD, Ngn3, or MafA, had a synergistic effect (97)(98)(99)(100)(101)(102)(103). Pancreatic ductal cells, which have been historically thought to contain putative b-cell progenitors, have also been subjected to similar transfection regimens, leading to significant upregulation of insulin expression.…”
Section: Cell Reprogrammingmentioning
confidence: 99%
“…To date, the process of transdifferentiation from hepatocytes to pancreatic tissue via the direct delivery of Pdx-1 has been performed on multiple occasions. 37,[120][121][122][123] However, direct delivery of Pdx-1 has been pursued in a variety of other cell types, including mouse pancreas via the bile duct, 124 rat intestinal epithelium-derived cells (IEC-6), 125 and primary …”
mentioning
confidence: 99%
“…However, most studies have reported low levels of insulin production after delivery of Neurog3. 121,126,[140][141][142] A study using adenoviral transfer of Neurog3 and betacellulin to oval cells resulted in the production of insulin and transdifferentiation; 143 however the most effective use of Neurog3 delivery was in combination with other transcription factors. 127 To successfully overcome the exocrine differentiation induced by the transfer of Pdx-1, Kojima et al expressed NeuroD1 and betacellulin in the livers of STZ-treated diabetic mice.…”
mentioning
confidence: 99%